Protection Of Post-Placement Indonesian Migrant Workers In Sampang Regency - Rosanawati, Resa; Ilhami, Fahri Nur; Prasetya, Ferry Wahyu; Rahayu, Devi (Fakultas Hukum, UPN Veteran Jawa Timur, 2021)
Protection of Indonesian Migrant Workers is an obligation of the state and also of the Government were to fulfill the rights of citizens, this protection does not only include during pre-placement and during placement but also post placement. Law No. 18 of 2017 concerning the protection of the migrant workers' placement is a legal umbrella that was formed to fulfill the rights of Indonesian Migrant Workers. As stated in Article 28 D paragraph 3, it reads that every citizen has the right to get a decent job. Where it is concluded that every citizen has the right to work abroad as well as its protection. The Covid-19 impact is very detrimental to PMIs, especially in terms of PMIs repatriation. The problem in this research is how to implement the protection of post-placement migrant workers. This research is an empirical research or approach research to society and the approach used is a fact approach. The results of this study examined the effectiveness of Law No. 18 of 2017 concerning the Protection of Indonesian Migrant Workers regarding the protection of Post-placement Migrant Workers.